The integration of yemen into the ottoman bureaucratic and central judicial system (1872-1918) - BOSTAN BERBER, HÜMEYRA (My University, 2022)
Abstract This article deals with the institutionalisation and bureaucratisation of the judicial system in the Ottoman province of Yemen in the late nineteenth and early twentieth centuries. During this period, the Ottoman central government gradually transformed and reorganised its judiciary, restricting the purview of the traditional şer\"iyye courts and increasing that of its new nizamiye courts. However, when the state attempted to incorporate its newly conquered province of Yemen into this new judicial system, it soon encountered problems. After abandoning the nizamiye courts, the government authorised the administrative councils and ser\"iyye courts to implement nizami law. I argue that the flexibility of Ottoman practices facilitated the gradual transformation of the legal system in Yemen, resulting in the re-establishment of the nizamiye courts with the agreement of local leaders. I also demonstrate that despite its efforts to centralise, the Ottoman state did not impose uniform policies and practices during the nineteenth century.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Hukuk; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SOSYOLOJİ; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; SOCIOLOGY; LAW; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Sociology and Political Science; Social Sciences & Humanities; Colonialism; Legal History; Nizamiye Courts; Ottoman Yemen; Sharia Courts; Ottoman Yemen; Legal History; Nizamiye Courts; Sharia Courts; colonialism